Cotargeting of miR‐126‐3p and miR‐221‐3p inhibits PIK3R2 and PTEN, reducing lung cancer growth and metastasis by blocking AKT and CXCR4 signalling. Issue 11 (21st July 2021) - Di Paolo, Daniela; Pontis, Francesca; Moro, Massimo; Centonze, Giovanni; Bertolini, Giulia; Milione, Massimo; Mensah, Mavis; Segale, Miriam; Petraroia, Ilaria; Borzi, Cristina; Suatoni, Paola; Brignole, Chiara; et al.
Abstract : Lung cancer is the leading cause of cancer‐related death worldwide. Late diagnosis and metastatic dissemination contribute to its low survival rate. Since microRNA (miRNA) deregulation triggers lung carcinogenesis, miRNAs might represent an interesting therapeutic tool for lung cancer management. We identified seven miRNAs, including miR‐126‐3p and miR‐221‐3p, that are deregulated in tumours compared with normal tissues in a series of 38 non‐small‐cell lung cancer patients. A negative correlation between these two miRNAs was associated with poor patient survival. Concomitant miR‐126‐3p replacement and miR‐221‐3p inhibition, but not modulation of either miRNA alone, reduced lung cancer cell viability by inhibiting AKT signalling. PIK3R2 and PTEN were validated as direct targets of miR‐126‐3p and miR‐221‐3p, respectively. Simultaneous miRNA modulation reduced metastatic dissemination of lung cancer cells both in vitro and in vivo through CXCR4 inhibition. Systemic delivery of a combination of miR‐126‐3p mimic and miR‐221‐3p inhibitor encapsulated in lipid nanoparticles reduced lung cancer patient‐derived xenograft growth through blockade of the PIK3R2–AKT pathway. Our findings reveal that cotargeting miR‐126‐3p and miR‐221‐3p to hamper both tumour growth and metastasis could be a new therapeutic approach for lung cancer. Abstract : Lung cancer is the first cause of cancer‐related deaths in the world. MicroRNAs are deregulated during lung carcinogenesis, and their modulation could represent an interesting therapeutic approach. We demonstrated that concomitant miR‐126 replacement and miR‐221 inhibition reduced lung cancer growth and metastasis both in vitro and in vivo . This study provides evidence for the use of miRNAs as therapy in lung cancer.